2019
DOI: 10.1038/s41598-019-44467-x
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Outcomes of Microvascular Reconstruction after Repeated Segmental Mandibulectomy in Head and Neck Cancer Patients

Abstract: This is the first study to investigate the impact of a second fibula flap or a soft tissue flap combined with bridging plate for a repeated segmental mandibulectomy reconstruction on flap outcomes in head and neck cancer patients. A retrospective comparative analysis (2007–2016) of 61 patients who underwent a second segmental mandibulectomy was performed. 20 patients underwent a fibula flap reconstruction whereas 41 had a soft tissue flap and plate reconstruction. No significant difference was seen in the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…There are varying reports of both higher and lower complication rates in bony flaps compared with soft tissue flaps in the literature, but interestingly, Frederick at al 25 in 2014 reported lower complication rates with fibula free flap transfer in general, at 2.9%, but this rate more than doubled to 6.3% in patients who underwent reconstruction for ORN rather than for oncologic ablation. [34][35][36] In our series, we have seen a significantly higher complication rate for patients receiving fibulae for reconstruction after ORN, at 100% (►Table 3), but this may be due to the elderly patient population used for this analysis having a higher rate of medical comorbidities. Regardless, there is insufficient literature to answer the question of whether patients receiving osteocutaneous free flaps consistently suffer a higher complication rate if ORN is involved when compared with resection of a primary tumor.…”
Section: Discussionmentioning
confidence: 73%
“…There are varying reports of both higher and lower complication rates in bony flaps compared with soft tissue flaps in the literature, but interestingly, Frederick at al 25 in 2014 reported lower complication rates with fibula free flap transfer in general, at 2.9%, but this rate more than doubled to 6.3% in patients who underwent reconstruction for ORN rather than for oncologic ablation. [34][35][36] In our series, we have seen a significantly higher complication rate for patients receiving fibulae for reconstruction after ORN, at 100% (►Table 3), but this may be due to the elderly patient population used for this analysis having a higher rate of medical comorbidities. Regardless, there is insufficient literature to answer the question of whether patients receiving osteocutaneous free flaps consistently suffer a higher complication rate if ORN is involved when compared with resection of a primary tumor.…”
Section: Discussionmentioning
confidence: 73%
“…reported 20 secondary mandibular reconstructions using FFF in patients with head and neck cancer. They demonstrated its advantages of lesser postoperative complications, such as recipient site infections and plate exposures, by comparing it with 41 secondary mandibular reconstructions using free soft tissue flaps combined with a bridging plate [ 12 ]. In both reports, the drawback of secondary mandibular reconstruction was the occurrence of scarring in recipient vessels and surrounding skin-soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In India, Kadam et al performed secondary mandibular reconstructions using FFF in 21 patients and reported ap survival and an improvement in symptoms that had necessitated secondary reconstruction in all patients [10]. In Taiwan, Lin et al reported 20 secondary mandibular reconstructions using FFF in patients with head and neck cancer and demonstrated its advantages of lesser postoperative complications, such as recipient site infections and plate exposures, by comparing it with 41 secondary mandibular reconstructions using free soft tissue aps combined with a bridging plate [11]. In both reports, the drawback of secondary mandibular reconstruction was the occurrence of scarring in recipient vessels and surrounding skin-soft tissues.…”
Section: Discussionmentioning
confidence: 99%